Palmeras utilizadas por los indígenas Yuracaré del Territorio Indígena Parque Nacional Isiboro-Sécure (Cochabamba, Bolivia) - Fabiola Montoya M.; Mónica Moraes R. (Revue d'ethnoécologie)
The Indigenous Territory National Park Isiboro Secure (TIPNIS in Spanish) is rich in biological diversity, and is inhabited by native groups, among them the Yuracaré. An ethnobotanical study was performed in five Yuracaré communities. The work consisted of semi-structured interviews and botanical collections of native palms, when was information on the uses and knowledge among men and women of different age. We also analyzed the difference of knowledge between different Yuracaré communities. There was a total of 14 species of useful palms, among the most important are Bactris gasipaes, Iriartea deltoidea and Astrocaryum gratum. In total 43 applications were identified, grouped into 22 subcategories and six categories: human food, construction, cultural, medicinal, products, tools and utensils. The community of San Antonio registered the largest diversity of palm uses, probably due to a low degree of disturbance and limited access to new technologies and services. The knowledge among men and women is similar; however the older people still own wisdom about uses of palm trees. The Yuracaré ethnic group lives depending on palm products and shows a close relationship with the surrounding forests where they are settled.